2003
DOI: 10.1148/rg.235035029
|View full text |Cite
|
Sign up to set email alerts
|

Urine Leaks and Urinomas: Diagnosis and Imaging-guided Intervention

Abstract: Urine leaks from the kidney, ureter, bladder, and urethra most commonly result from trauma. Urinomas may be occult initially and may lead to complications such as abscess formation and electrolyte imbalances if not promptly diagnosed and appropriately managed. Radiologists play a key role in diagnosing urine leaks and determining their cause and extent. Contrast material-enhanced computed tomography (CT) with delayed imaging, CT cystography, and retrograde urethrography are the diagnostic imaging studies of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
162
0
17

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(181 citation statements)
references
References 13 publications
2
162
0
17
Order By: Relevance
“…The most useful imaging study to identify cystic or solid masses with calcifications is abdominal CT. Additionally, delayed images usually show extravasation of the contrast medium and provides information regarding the perforation site. [6,7] In the present study, we confirmed not only the contrast medium extravasation but also showed extruded calculus in the perirenal space by contrastenhanced CT study. To avoid unnecessary exposure to radiation to a growing female child, we only followed the patient with plain roentgenogram and ultrasound studies; hence, we did not perform a second CT after no calculus was revealed in plain X-ray and ultrasonographic images.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The most useful imaging study to identify cystic or solid masses with calcifications is abdominal CT. Additionally, delayed images usually show extravasation of the contrast medium and provides information regarding the perforation site. [6,7] In the present study, we confirmed not only the contrast medium extravasation but also showed extruded calculus in the perirenal space by contrastenhanced CT study. To avoid unnecessary exposure to radiation to a growing female child, we only followed the patient with plain roentgenogram and ultrasound studies; hence, we did not perform a second CT after no calculus was revealed in plain X-ray and ultrasonographic images.…”
Section: Discussionsupporting
confidence: 85%
“…Additional use of a Unusual complication of a urinary stone in a child: spontaneous rupture of the renal pelvis with the migration of calculus into the retroperitoneum nephrostomy catheter or a ureteral stent with a percutaneous drainage catheter improves the diversion of the urine from the ruptured area and accelerates healing of the injured collecting system. [7] In our case, we initially placed an ultrasound-guided drainage catheter into the urinoma; then, the placement of a JJ stent was attempted but was unsuccessful. The catheter was kept for 4 weeks until the urine output stopped by the end of this 4-week period.…”
Section: Discussionmentioning
confidence: 90%
“…However, the urologic trauma literature supports the use of a ureteral stent in the management of a collecting system injury, suggesting that such an approach would be appropriate also after PCNL (29). The retrospective nature of our study carries inherent risk for selection bias; prospective randomized trials would more definitively address the questions posed.…”
Section: Discussionmentioning
confidence: 94%
“…Indications for contrast-enhanced CT evaluation (based on unenhanced CT findings) are: i) presence of unilateral perinephric stranding without hydroureteronephrosis with or without renal enlargement (acute renal infarction, renal vein thrombosis, acute pyelonephritis); ii) significant hypo-/ hyperdense perirenal collection (urinoma, hematoma) with or without the b a presence of hydroureteronephrosis; iii) presence of a mass or complicated cyst with/without calculus; iv) negative unenhanced CT findings in a patient with unexplained hematuria (52). Common clinical conditions requiring contrastenhanced CT after unenhanced CT scan in a patient presenting with flank pain and hematuria are infections, neoplasms, renal cyst complications, vascular lesions, urinoma and acute perirenal hematoma, of which imaging findings are already defined elsewhere (51)(52)(53)(54)(55).…”
Section: When Should the Intravenous Contrast Be Given?mentioning
confidence: 99%